APPLICATION OF DIFFERENTIAL EQUATIONS IN POPULATION GROWTH ESTIMATION OF KEDIRI CITY AS THE IMPLEMENTATION OF THE 2030 SDGS TARGET - Andini, Nova; Hamidah, Dewi; Surur, Agus Miftakus (PATTIMURA UNIVERSITY, 2024)
This study focuses on analyzing the application of differential equations in modeling the population growth of Kediri City through a logistic growth model, and aims to predict the city's population for the years 2021-2030. Employing a literature study approach, this research utilizes secondary data sourced from the official website of the BPS (Central Statistics Agency) of Kediri City. The data encompasses population figures from 2005 to 2020. To ensure the accuracy of the population predictions made by the logistic growth model, a comparison with the official data from the Central Statistics Agency is necessary. A critical aspect of this research involves estimating the carrying capacity of Kediri City's population, which is identified as 295,672 individuals in the year 2030. The findings indicate a significant growth trend in the population, characterized by a specific growth rate. To validate the accuracy of the logistic growth model, the Mean Absolute Percentage Error (MAPE) method was applied, resulting in an error percentage that falls within the highly accurate category, thus affirming the reliability of the model in predicting population growth trends.